2017
DOI: 10.3847/1538-4357/aa56c7
|View full text |Cite
|
Sign up to set email alerts
|

Stellar and Planetary Parameters for K2's Late-type Dwarf Systems from C1 to C5

Abstract: The NASA K2 mission uses photometry to find planets transiting stars of various types. M dwarfs are of high interest since they host more short-period planets than any other type of main-sequence star and transiting planets around M dwarfs have deeper transits compared to other main-sequence stars. In this paper, we present stellar parameters from K and M dwarfs hosting transiting planet candidates discovered by our team. Using the SOFI spectrograph on the European Southern Observatory's New Technology Telesco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 79 publications
(131 reference statements)
7
30
0
Order By: Relevance
“…We note that our radius estimates for all four planets are consistent with the revised values found by Martinez et al (2017), who used NTT/SOFI spectroscopy to characterize the host star and then scaled the R p /R å values from Crossfield et al (2016) accordingly.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…We note that our radius estimates for all four planets are consistent with the revised values found by Martinez et al (2017), who used NTT/SOFI spectroscopy to characterize the host star and then scaled the R p /R å values from Crossfield et al (2016) accordingly.…”
supporting
confidence: 74%
“…As expected, Figure 2 also reveals that K2OIs with high FPPs tend to be larger than those with lower FPPs. Martinez et al (2017) noted a similar size difference between the radii of their planet candidates and validated planets (see their Figure 9) and remarked that the radius estimates for candidates tend to be more uncertain. The primary difference between our K2 planet candidates and the Kepler sample is that the K2 sample is biased toward brighter host stars.…”
Section: Revised Planet Propertiesmentioning
confidence: 98%
“…Planets of M-dwarfs have on average smaller sizes than planets of Solarlike stars (Martinez et al, 2017). This observational fact may provide another answer to the problem of formation of planets of terrestrial type, again pointing out that abiogenesis can be concentrated on CBP of double Mdwarfs.…”
Section: Habitability Of Cbp Of M-dwarf Binariesmentioning
confidence: 75%
“…We also found that inputting 2MASS photometry into isochrones along with the aforementioned stellar parameters had no noticeable effect on the resulting stellar radius and mass values (or their uncertainties). Although isochrones have been found to underestimate stellar radii before (Dressing et al 2017a(Dressing et al , 2017bMartinez et al 2017), this effect is confined to M dwarfs and late-K dwarfs, which are largely excluded from our host star sample since we do not consider stars with effective temperatures below 4250 K (see Section 4.2). The derived stellar masses and radii are reported in Table 2.…”
Section: Full Validation Resultsmentioning
confidence: 99%
“…K2 has led to the discovery of numerous candidate and confirmed planets Foreman-Mackey et al 2015;Montet et al 2015;Vanderburg et al 2015bVanderburg et al , 2016bAdams et al 2016;Barros et al 2016;Crossfield et al 2016;Schlieder et al 2016;Sinukoff et al 2016;Pope et al 2016;Dressing et al 2017b;Hirano et al 2017;Martinez et al 2017), as well as to the identification of planets orbiting rare types of stars, including particularly bright nearby dwarf stars Vanderburg et al 2016a;Christiansen et al 2017;Crossfield et al 2017;Niraula et al 2017;Rodriguez et al 2017aRodriguez et al , 2017b, young, pre-main-sequence stars (Mann et al 2016;David et al 2016), and disintegrating planetary material transiting a white dwarf (Vanderburg et al 2015a).…”
Section: Introductionmentioning
confidence: 99%